Factors Predicting Length of Hospital Stay among Patients with Open-Heart Surgery - Piwpong, Ratchanee; Kongprom, Supaporn; Suksumitr, Nantaka; Durongrittichai, Vanida (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 4 (2020): October-December-2020DO - 10.14456/nujst.2020.33, 2020)
Factors predicting the length of hospital stay among patients with open-heart surgery, basic information for use in the planning of care for postoperative heart patients to have higher quality and efficiency. This study was descriptive research with a retrospective methodology aimed at studying the factors predicting length of hospital stay in open-heart surgery patients. The sample was composed of 214 open-heart surgery patients who were purposively sampled based on set inclusion criteria. Data were collected from medical records in 2015 – 2016. Data were analyzed with descriptive statistics, Pearson’s Product Moment Correlation and multiple linear regression. According to the findings, the variables correlated with length of hospital stay in open-heart surgery patients with statistical significance were age, diabetes mellitus, coronary artery bypass surgery, urgency of surgery and cardiopulmonary bypass time. The factors capable of predicting length of hospital stay in open-heart surgery patients were urgency of surgery (beta = .22), cardiopulmonary bypass time (beta = .19) and age (beta = .16). All of the factors were able to co-predict fluctuations in length of hospital stay among open-heart surgery patients at 15 percent (R2 = 0.15, F = 5.04, p < .001). Therefore, elderly open-heart surgery patients who went into surgery urgently and had long cardiopulmonary bypass time should have special care models or close monitoring of symptoms to help reduce length of hospital stay in this group of patients. Keywords: Factors Predicting, Length of Hospital Stay, Patients with Open-Heart Surgery